The association of artificial sweeteners intake and risk of cancer: an umbrella meta-analysis - Abu-Zaid, Ahmed; Kutbi, Emad; Alshammari, Nawal; AlJurayyan, Abdullah Nasser; Adly, Heba M.; Saleh, Saleh A. K.; Baradwan, Saeed; Jamal, Madiha; Peer-Zada, Feham; Mohamed, Shaimaa; Syed, Huda; Ahmed, Rania Salah; et al. (Frontiers in Medicine, 2025)
BackgroundPrevious meta-analyses exploring the relationship between artificial sweetener consumption and cancer risk have shown inconsistent results. To address these discrepancies, we conducted an umbrella review of systematic reviews and meta-analyses of observational studies.MethodsWe systematically searched PubMed, Scopus, and Web of Science up to January 2025. Pooled relative risks (RRs) and 95% confidence intervals (CIs) were recalculated using a random-effects model. Subgroup and sensitivity analyses assessed the robustness of findings.ResultsTen meta-analyses comprising 35 datasets were included. Based on the AMSTAR 2 tool, three reviews were rated as high quality, two as moderate, and five as low. Overall, artificial sweetener intake was not significantly associated with cancer risk (RR: 0.99; 95% CI: 0.96–1.01). This finding reflects the effect of various sweeteners grouped together and should not be extrapolated to individual compounds. Sensitivity analyses confirmed the robustness of findings, with no publication bias detected. Across study designs—prospective (RR: 1.00; 95% CI: 0.92–1.08), case-control (RR: 0.94; 95% CI: 0.86–1.03), and cohort–case-control (RR: 0.96; 95% CI: 0.77–1.14)—associations were consistently non-significant. By sweetener source, no significant associations emerged for artificially sweetened beverages (RR: 0.98; 95% CI: 0.96–1.01) or artificial sweeteners overall (RR: 1.00; 95% CI: 0.94–1.06), both with low heterogeneity. Results were consistent across RR, odds ratio, and hazard ratio. By cancer type, no significant associations were found except for gynecological cancers, where higher intake was linked to reduced risk (RR: 0.87; 95% CI: 0.79–0.96; I2 = 0%).ConclusionThe findings of this umbrella review do not support a significant association between artificial sweetener intake and overall cancer risk, with possible protective effects limited to gynecological cancers. Findings were consistent across study types and robust to sensitivity analyses.